2010
DOI: 10.1007/s12204-010-8707-4
|View full text |Cite
|
Sign up to set email alerts
|

Path following control of underactuated ships based on unscented Kalman filter

Abstract: A path following controller is proposed to force an underactuated surface ship which is suffering from disturbance to follow a predefined path. The controller is based on analytic model predictive control and unscented Kalman filter (UKF) techniques. The analytic model predictive control provides a systematic method to get appropriate controller parameters to guarantee the stability of the closed-loop system, and the well-defined relative degree is guaranteed by introducing output-redefinition. The UKF is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The method proposed in the article can reduce the calculation complexity and save time. The reference equation in this method is equation (3), where ˆ( , ) f x τ is simpler than ( , ) f x τ in the equation (2) which is the reference equation of the nominal SVDUKF. Comparing the two, we can see the calculation of every sigma point reduces 20 multiplications and 15 additions.…”
Section: Analysis Singular Value Decomposition Ukf Based On Accelerat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The method proposed in the article can reduce the calculation complexity and save time. The reference equation in this method is equation (3), where ˆ( , ) f x τ is simpler than ( , ) f x τ in the equation (2) which is the reference equation of the nominal SVDUKF. Comparing the two, we can see the calculation of every sigma point reduces 20 multiplications and 15 additions.…”
Section: Analysis Singular Value Decomposition Ukf Based On Accelerat...mentioning
confidence: 99%
“…In recent years, UKF has obtained extensive attentions, and many researches on the performance of UKF can be found. For instance, UKF has been introduced into the aircrafts modeling [1] , Wang et al [2] studied UKF parameters estimation based on nonlinear observation and nonlinear kinetics model of the under-actuated ship, and then designed a predictive controller; Peng et al [3] estimated the uncertainty of the ship model and designed a nonlinear controller.…”
Section: Introductionmentioning
confidence: 99%
“…An unscented Kalman filter (UKF)-based tracking controller is proposed in Peng et al (2007) combined with backstepping techniques to force an UAV to follow a reference path under constant disturbances, wherein the UKF is used to online update system states and time-varying uncertain parameters to achieve accurate tracking performance. Based on analytic MPC and UKF, a path following controller is proposed in Wang et al (2010) to maneuver an underactuated ship suffering from external disturbances along a desired straight path, and the UKF is used to estimate the states and uncertain parameters. Moreover, some work focuses on addressing unknown process and measurement noise covariance matrices (Huang et al, 2018b), especially heavy-tailed noises (Huang et al, 2017b;Huang et al, 2018a;Huang et al, 2017a;Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cement morta,cement slurry and other series of materials,low-cost,fire resistance,heat resistance, excellent corrosion resistance,compressive strength is also high,so has been widely used in marine engineering and construction.But there are some shortcomings of their own,such as easily plastic shrinkage cracking,bad impact toughness, low fracture toughness and such nature vulnerability,thus limiting their more widely used in projects. Adding fibers in the matrix is an effective means to improve its performance,carbon fiber as a synthetic fiber,has high strength,modulus,corrosion resistance and other characteristics,so it has been widely used in the field of concrete products.There have been so many research reports on carbon fiber's effect on properties of cement based materials at home and abroad [1][2][3],and have also made many valuable research results. The basalt fibers is a new kind of inorganic fiber material, which is a kind of fiber got by rapidly drawing un cement-based materials can improve cement products inherent brittleness and so that to improve performance of cement-based materials [4] .Some studies have shown: the incorporation of basalt fiber makes cement-based material own defect such as easy shrinkage cracking, low flexural strength, toughness and poor function were significantly improved [5,6].…”
Section: Introductionmentioning
confidence: 99%